The neuroscience of body memory: From the self through the space to the others. (July 2018) - Riva, Giuseppe
Abstract: Our experience of the body is not direct; rather, it is mediated by perceptual information, influenced by internal information, and recalibrated through stored implicit and explicit body representation (body memory). This paper presents an overview of the current investigations related to body memory by bringing together recent studies from neuropsychology, neuroscience, and evolutionary and cognitive psychology. To do so, in the paper, I explore the origin of representations of human body to elucidate their developmental process and, in particular, their relationship with more explicit concepts of self. First, it is suggested that our bodily experience is constructed from early development through the continuous integration of sensory and cultural data from six different representations of the body, i.e., the Sentient Body (Minimal Selfhood), the Spatial Body (Self Location), the Active Body (Agency), the Personal Body (Whole Body Ownership – Me); the Objectified Body (Objectified Self – Mine), and the Social Body (Body Satisfaction – Ideal Me). Then, it is suggested that these six representations can be combined in a coherent supramodal representation, i.e. the "body matrix", through a predictive, multisensory processing activated by central, top–down, attentional processes. From an evolutionary perspective, the main goal of the body matrix is to allow the self to protect and extend its boundaries at both the homeostatic and psychological levels. From one perspective, the self extends its boundaries (peripersonal space) through the enactment and recognition of motor schemas. From another perspective, the body matrix, by defining the boundaries of the body, also defines where the self is present, i.e., in the body that is processed by the body matrix as the most likely to be its one, and in the space surrounding it. In the paper I also introduce and discuss the concept of "embodied medicine": the use of advanced technology for altering the body matrix with the goal of improving our health and well-being.